Two novel homozygous SLC2A9 mutations cause renal hypouricemia type 2 - Dinour, D.; Gray, N. K.; Ganon, L.; Knox, A. J. S.; Shalev, H.; Sela, B.-A.; Campbell, S.; Sawyer, L.; Shu, X.; Valsamidou, E.; Landau, D.; Wright, A. F.; et al. (Nephrology, dialysis, transplantation, 2012)
Elevated serum uric acid (UA) is associated with gout, hypertension, cardiovascular and renal disease. Hereditary renal hypouricemia type 1 (RHUC1) is caused by mutations in the renal tubular UA transporter URAT1 and can be complicated by nephrolithiasis and exercise-induced acute renal failure (EIARF). We have recently shown that loss-of-function homozygous mutations of another UA transporter, GLUT9, cause a severe type of hereditary renal hypouricemia with similar complications (RHUC2). Two unrelated families with renal hypouricemia were clinically characterized. DNA was extracted and SLC22A12 and SLC2A9 coding for URAT1 and GLUT9, respectively, were sequenced. Transport studies into Xenopus laevis oocytes were utilized to evaluate the function of the GLUT9 mutations found. A molecular modeling study was undertaken to structurally characterize and probe the effects of these mutations. Two novel homozygous GLUT9 missense mutations were identified: R171C and T125M. Mean serum UA level of the four homozygous subjects was 0.15 ± 0.06 mg/dL and fractional excretion of UA was 89-150%. None of the affected subjects had nephrolithiasis, EIARF or any other complications. Transport assays revealed that both mutant proteins had a dramatically reduced ability to transport UA. Modeling showed that both R171C and T125M mutations are located within the inner channel that transports UA between the cytoplasmic and extracellular regions. This is the second report of renal hypouricemia caused by homozygous GLUT9 mutations. Our findings confirm the pivotal role of GLUT9 in UA transport and highlight the similarities and differences between RHUC1 and RHUC2.